Increasing smart city competitiveness and sustainability through managing structural capital - Matos, F.; Vairinhos, V. M.; Dameri. R. P.; Durst, S. (Journal of Intellectual Capital, 2017)
Purpose: The purpose of this paper is to explore and discuss possible solutions to integrate the concepts of smart city (SC) and intellectual capital management, especially referring to structural capital. On the basis of this, the authors propose a theoretical framework that highlights the relevance of structural capital for strategic and operational planning of smarter cities. Design/methodology/approach: Using a neuropsychological analogy, the authors assume that the development of SCs corresponds to the development of a sensorial or even a nervous system for cities based on their structural capital, and the development of city intellectual capital (CIC) corresponds to a further phase of the cities’ mind development. The authors propose a practical framework that combines the concepts of city nervous system and city mind. It can be used as an instrument for project management. In this model, sensorial data – associated with the implementation of cities’ sensorial systems – should naturally contribute with open data to the development of higher abstract functions that in turn supports the creation of CIC. Findings: This paper highlights the interrelations between intellectual capital (IC) (especially its structural component) and SC and their synergic capability of improving both an SC’s competitiveness and sustainability, and by this illustrates the benefits of combining both concepts in a common theoretical framework. Research limitations/implications: Given the paper’s theoretical nature, the empirical validation of the proposed framework is missing. This limitation will be addressed in forthcoming empirical research. Originality/value: By proposing a framework that combines the concepts of SC and IC, the paper contributes to theory development regarding the strategic management of cities and the application of IC.